2020
DOI: 10.3892/ol.2020.11609
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from endoplasmic reticulum‑stressed liver cancer cells enhance the expression of cytokines in macrophages via the STAT3 signaling pathway

Abstract: Previous studies have shown that endoplasmic reticulum (ER) stress serves an important role in shaping the immunosuppressive microenvironment by modulating resident immune cells. However, the communication between ER-stressed tumor cells and immune cells is not fully understood. Exosomes have been reported to play a vital role in intercellular communication. Therefore, in order to investigate the role of ER stress-related exosomes in liver cancer cells mediated macrophage function remodeling, immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Almost all types of normal cells can produce exosomes, like human umbilical vein endothelial cells, mesenchymal stem cells (MSC), T cells, B cells, macrophages, dendritic cells (DC), natural killer (NK) cells. [19][20][21][22] For example, mesenchymal stem cells (MSCS) are pluripotent stem cells capable of self-renewal and multidirectional differentiation. MSCs can not only adapt to the tumor microenvironment, but also have powerful paracrine activity and secrete a large number of exosomes.…”
Section: Classificationmentioning
confidence: 99%
“…Almost all types of normal cells can produce exosomes, like human umbilical vein endothelial cells, mesenchymal stem cells (MSC), T cells, B cells, macrophages, dendritic cells (DC), natural killer (NK) cells. [19][20][21][22] For example, mesenchymal stem cells (MSCS) are pluripotent stem cells capable of self-renewal and multidirectional differentiation. MSCs can not only adapt to the tumor microenvironment, but also have powerful paracrine activity and secrete a large number of exosomes.…”
Section: Classificationmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress can impede the development of antitumor immune responses through reprogramming of several immune cell populations [116,117]. In macrophages, exosomes derived from liver cancer cells undergoing ER stress promoted the secretion of IL-6, MCP-1, IL-10, and TNF-a through STAT3 signaling [118]. Another study has shown that exosomal miR-27a-3p released from breast cancer cells undergoing ER stress promoted immune evasion through up-regulation of PD-L1 expression in macrophages [119].…”
Section: Macrophagesmentioning
confidence: 99%
“…ER stress-associated exosomes mediate macrophage cytokine secretion in the liver cancer microenvironment, and also indicate the potential of treating liver cancer via an ER stress-exosomal-STAT3 pathway. 128 Mesenchymal stem cell-derived exosomal miR-223 protects neuronal cells from apoptosis, enhances cell migration and increases miR-223 by targeting PTEN, thus activating the PI3K/Akt pathway. In addition, exosomes isolated from the serum of AD patients promote cell apoptosis through the PTEN-PI3K/Akt pathway and these studies indicate a potential therapeutic approach for AD.…”
Section: Bio-functions Of Exosomesmentioning
confidence: 99%